EFFICIENT SYNTHESIS OF ZNO AS AN ELECTRODE OF PIEZOELECTRIC NANOGENERATORS - Salh, Ribar A.; Ibrahem, Mohammed A. (Science Journal of University of Zakho, 2024)
Piezoelectric nanogenerators (NGs) hold immense promise as self-powered devices for harvesting mechanical energy from the environment. This study introduces an efficient and scalable synthesis method for zinc oxide (ZnO) nanorods, a pivotal material in piezoelectric nanogenerators (NGs), with several key results. A Chemical Bath Deposition technique is employed, optimizing parameters such as growth time, temperature, and precursor concentrations to achieve well-aligned and high-quality ZnO nanorods. The structural and morphological characteristics of the synthesized nanorods are systematically investigated using advanced characterization techniques. The synthesized ZnO nanorods exhibit an average length of 400nm, demonstrating their slender shape. Furthermore, the study determines an energy gap value of 3.5 eV for multilayer zinc oxide thin films, indicating the transition from the valence band to the conduction band. Notably, thermal annealing at 500°C leads to a substantial increase in average output voltage, reaching 1.95 V, a fourfold improvement compared to as-deposited nanopowders. These findings emphasize the efficiency and potential of the proposed synthesis method and underscore its practical applications in enhancing energy harvesting capabilities for sustainable power generation from mechanical sources in piezoelectric NGs.